Pengaruh Pemberian Pupuk Kandang Ayam dan Berbagai Dosis Pupuk Urea Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guien eensis Jacq.) di Main Nursery - Gunawan '; Erlida Ariani; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the effect of chiken manure and various doses of urea fertilizer on Palm Oil seedling growth (Elaeis guineensis Jacq) in the Main Nursery, as well as to obtain the best combination of treatments. This research lasted from August 2013 to November 2013 at Agriculture Faculty, University of Riau. Research arranged experimentally using Completely Randomized Design (CRD), 2 factors with 3 replications. First factor: Chiken Manure K0 (Without treatment) K1 (25 g/polybag) and K2 (50 g / polybagy), and second factor: Urea Fertilizer U0 (without treatment), U1 (0.45 g/polybag) U2 (0.91g/polybag) and U3 (1.82 g/polybag). Parameters measured were additional seeds height, additonal stump diameter, additional number of leaves, root volume, shoot root ratio and dry weight. Data were analyzed using the F test and test of Duncan New’s Multiple Range Test (DNMRT) 5%. The results shows the use of chicken manure reveal significant value on increasing the stump diameter, shoot root ratio and dry weight of plants and the use of urea fertilizer effect on all parameters, increasing the plant height, diameter of the stump, number of leaves, root volume, shoot root ratio and dry weight of plants, while the combination of chiken manure and urea fertilizer reveal no effect on all parameters. Keywords: Chiken manure, Urea Fertilizer, main nursery and palm oil(Elaeis guieneensis Jacq.)